In vitro Root Culture : An Alternative Source of Bioactives in the Rare Aphrodisiac Herb Chlorophytum borivilianum Sant et Fern (Plant Tissue Culture and Biotechnology, 2014)
Chlorophytum borivilianum is a rare, near-endemic high value root crop. The fasciculated roots of the plant have the potential to synthesize valuable bioactives having aphrodisiac, anti stress and immuno modulatory properties. The present investigation describes an alternative protocol for the development of a stable, fast growing, non-transformed root culture system in C. borivilianum and the simultaneous quantitative analysis of total steroidal saponins, amino acids and sugars. Liquid MS fortified with various concentrations and combinations of BA (0.44 - 8.8 µM), Kn (0.23 µM) and NAA (0.27 - 5.4 µM) was effectively used for the development of root culture system. High performance thin layer chromatography (HPTLC) was used for quantification and comparative analysis of bioactives from in vitro and in vivo grown tuberous roots. D. O. I.  http://dx.doi.org/10.3329/ptcb.v23i2.17505 Plant Tissue Cult. & Biotech. 23(2): 133-146, 2013  (December)